Chondroma of laryngeal cartilage mimicking thyroid tumor: A case report. Issue 13 (March 2019) - Tan, ZiQiao; Yao, Mengwei; Liu, Tao; Wang, Shaohua; Xu, Jing; Zhang, Yonghong; Yang, Xinxin; Ma, Dengdian; Li, Xiaoyu
Abstract: Rationale: Cartilaginous tumors of the larynx are rare. This report describes an atypical case with chondroma of laryngeal cartilage presenting as cervical mass, which was misdiagnosed as a thyroid tumor. Patient concern: A 73-year-old Chinese man with a 1-month history of cervical mass. The neck color Doppler ultrasound and CT of thyroid showed a space-occupying lesion in the upper right pole of the thyroid gland. Diagnoses: Chondroma of laryngeal cartilage was confirmed at the time of surgery. Interventions: After relevant examinations, subtotal thyroidectomy and excisional biopsy of the neck mass were performed under general anesthesia. However, the rapid pathology of the tumor (thyroid right lateral lobe) indicated chondroma, so the patient underwent laryngeal chondroma resection and tracheotomy under general anesthesia. Outcomes: After surgery, given the advanced age of the patient, long surgical duration and poor cardiorespiratory function, the patient suffered sudden cardiac death after the operation. Lessons: Cartilaginous tumor of the larynx is rare, and approximately 250 cases have been reported till date. It is difficult to diagnose cartilaginous tumors of the larynx in the early stage, and they are easily misdiagnosed. Early diagnosis, radical surgery, and long-term follow-up are key to prolong survival.